Anti-Nutrient, Phytochemical and Free Fatty Acid Composition of Dehulled and Undehulled Sweet Princess Watermelon (Citrullus lanatus) Seed Flour - Vivienne, Ibeanu N.; Uchenna, Onyechi A.; Peace, Ani N.; Vivian, Aneke C. (Pakistan Journal of Nutrition, 2014)
Dietary alterations have strong effects (both positive and negative) on health throughout life. Nutrition transition is implicated with the development of chronic non communicable diseases (NCD) and these are risk factors of disabilities and premature death in developing countries. Legumes have been shown to play important role in the prevention of NCD because of their constituents. This study assessed anti-nutrient, phytochemical and free fatty acid composition of dehulled and undehulled sweet princess watermelon (Citrullus lanatus) seed flour. Seeds were extracted manually from fresh ready-to-eat sweet princess watermelon fruit purchased from a local market in Enugu State, Nigeria. Water was used to wash off pulp on seeds before sun-drying for 72 h. The dried seeds were divided into two portions, one dehulled manually and milled and the other milled undehulled. Anti-nutrient, phytochemical and free fatty acids composition of the samples was determined in triplicate using standard procedures. Means were statistically separated and compared. The undehulled sample contained significantly (p